Problematika Dan Strategi Optimalisasi Sertifikasi Halal Di Indonesia - Usnan Usnan; Aisy Rahmadani; Kortis Luhut Maharani (Journal of Islamic Economics and Finance, 2024)
This research was conducted with the aim for analyzing and mapping problems in the implementation of halal certification for micro and small enterprises (UMK) in Indonesia. This research uses a qualitative method with a literature study approach, namely by searching for articles via Google Scientist with the keywords halal certification problems, then reviewing and mapping the research findings obtained. The results of this research show that from the 12 papers reviewed, 4 (four) classifications of problems in the implementation of halal certification policies can be mapped, namely first, regulatory aspects, second, perceptions and behavior of MSE actors, third, knowledge aspects and fourth, support system aspects. The efforts put forward by researchers from the four problem maps are (1) carrying out evaluations and reviews of regulations, (2) carrying out comprehensive, systematic and measurable outreach and education efforts, and (3) improving existing infrastructure and personnel in the implementation of halal certification.